Revisiting the Great Moderation: policy or luck? - Patrick Minford; Zhirong Ou; Michael Wickens (Cardiff University, Cardiff Business School, 2014)
We investigate the relative roles of monetary policy and shocks in causing the Great Moderation, using indirect inference where a DSGE model is tested for its ability to mimic a VAR describing the data. A New Keynesian model with a Taylor Rule and one with the Optimal Timeless Rule are both tested. The latter easily dominates, whether calibrated or estimated, implying that the Fed's policy in the 1970s was neither inadequate nor a cause of indeterminacy; it was both optimal and essentially unchanged during the 1980s. By implication it was largely the reduced shocks that caused the Great Moderation - among them monetary policy shocks the Fed injected into inflation.
Keywords: E42; E52; E58; 330; Great Moderation; Causes; Indirect inference; Test; Wald statistics